Сучасний стан систематики грибів підвідділу Pucciniomycotina - Тихоненко, Ю.Я. (Український ботанічний журнал, 2010)
Статья представляет собой обзор современных работ по систематике подотдела Pucciniomycotina. В соответствии с современными взглядами он включает 8 классов: Agaricostilbomycetes, Atractiellomycetes, Classiculomycetes, Cryptomycocolacomycetes, Cystobasidiomycetes, Microbotryomycetes, Myxiomycetes и Pucciniomycetes. Наибольшим разнообразием среди них выделяется класс Pucciniomycetes – около 8000 видов. Recent publications on systematics of the subdivision Pucciniomycotina are surveyed. According to modern opinions, this subdivision comprises 8 classes: Agaricostilbomycetes, Atractiellomycetes, Cla ssiculomycetes, Cryptomycocolacomycetes, Cystobasidiomycetes, Microbotryomycetes, Myxiomy cetes and Pucciniomycetes. The most diverse of them is Pucciniomycetes – about 8000 species.